Purification, crystallization and molecular modeling of recombinant A3 lipase from an antartic Pseudomonas sp. strain AMS3 - Leong, Mun Hong (2015)
A recombinant A3 lipase from Pseudomonas sp. strain AMS 3 was previously expressed in E. coli. In present study, recombinant A3 lipase was successfully purified through Nickel-Sepharose Fast Flow affinity chromatography. This purification recovered 58.47% of yield with the purification fold 3.69. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) was used to determine the molecular weight of purified A3 lipase. A3 lipase was screened for crystal under crystallization condition of Crystal Screen and Crystal Screen 2 from Hampton Research in MRC 2 well crystallization plate (Swissci) with the aid of crystallization robot, Oryx 8 for crystallization hits from the screening. The best A3 lipase crystal being observed in the formulation of 0.5 M ammonium sulfate, 0.1 M HEPES pH 7.5 and 30% v/v (+/-)-2-methyl-2,4-pentanediol. 3D structure of A3 lipase was predicted from RaptorX and analyzed by YASARA software. The predicted 3D structure of A3 lipase contained catalytic triad covered with 2 lid subunits, 2 metal ions binding site and glutathione-s-transferase located at the N-terminal.